Editorial - Melba Libia Cárdenas (Profile Issues in Teachers' Professional Development, 2010)
I am delighted to start this editorial by sharing with all of you the recognition granted recently by Publindex-Colciencias, which is the national indexing system for Colombian journals. The high standards of PROFILE have been acknowledged one more time and for this reason, we have been classified in category A2.